Upaya Pekerja Outsourcing Terhadap Pemutusan Hubungan Kerja Atas Pelanggaran Kontrak Kerja - I Putu Agus Tirta Yasa; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2020)
In its development, every industry today is a business activity that produces a large economy that requires a lot of labor. In its rules namely Law No. 13 of 2003 which applies primarily in labor matters has been established as a rule for systematically running the business activities of the company. The formulation of the problem in this study is 1) How do acts of violation of termination of employment against outsourcing workers? 2) What are the efforts of outsourcing workers who violate the employment contract and are affected by Termination of Employment? This study uses normative legal research methods, uses the statutory approach and conceptual approach, examines primary legal materials, secondary legal materials, and tertiary legal materials and uses legal material collection techniques by studying literature, reading literature and related internet pages. Outsourcing is a term that refers to the authority of the job to employ every community who wants to move in the company's business. Outsourcing workers are intended as workers who have joined certain companies to carry out a business activity in which of course there are terms and conditions governing the management of these workers, mentioned in the employment contract. The rules contained in each work contract allow there is no crime against business ventures and layoffs if there is fraud or breach of contract outsourcing workers in running a business, it is in accordance with the Manpower Act.